Tax Evasion and Collection in Commercial Companies of the Tacna Region - Moscoso, Giomar (2019)
Tax evasion and tax collection in small and medium-sized enterprises in the region is a persistent and growing problem that affects not only the fiscal fund but also the development of the country. Therefore, knowing from the perspective of the family business how this phenomenon happens is important to understand the problem and in subsequent work to initiate the corresponding improvement actions. The work aims to determine if there is a relationship between Tax Evasion and Tax Collection in merchants of the Lima Fair in the province of Tacna. Its secondary objectives are: To determine the relationship between Tax Consciousness and Tax Collection, determine the relationship between fiscal responsibility as a role of the taxpayer and Tax Collection and analyze tax knowledge and its relationship with tax collection in the companies investigated. The study carried out belongs to the exploratory, descriptive, relational level and presents a non-experimental and transectional design. According to the objective of the research, the aim is to find the relationship of the variables, it is defined as a descriptive-correlational study. As a result, it was concluded that there is a significant relationship between tax evasion and tax collection in merchants of the Lima Fair in the province of Tacna 2017. Likewise, it is proved that there is a significant relationship between tax awareness and tax collection in merchants of the Lima Fair in the province of Tacna. In the same sense, it can be indicated that fiscal responsibility as a role of the taxpayer has a significant relationship in tax collection in merchants of the Lima Fair in the province of Tacna, and finally there is a significant relationship between tax knowledge and Tax collection in the merchants of the Lima Fair in the province of Tacna year 2017.